SUBSTANCE USE, DEPRESSION, ANXIETY AND STRESS AMONG UNIVERSITY STUDENTS (The Research of Medical Science Review, 2025)
Depression, anxiety, stress, and substance use pose major public health concerns. Substance use negatively impacts mental health. Excessive drug use often exacerbates symptoms of depression, anxiety, and stress, leading to adverse health outcomes. This study aims to investigate the relationship between substance use and depression, anxiety, and stress among university students. Using purposive sampling, a sample of 60 university students aged 17 to over 30 was recruited from various universities in Rawalpindi and Islamabad. The research employed a correlational design, utilizing the Depression, Anxiety, and Stress Scale - 21 Items (DASS-21) and the Drug Abuse Screening Test (DAST-10) for data collection. Pearson correlation analysis revealed a significant positive relationship between substance use and symptoms of depression, anxiety, and stress. The findings underscore the need for interventions targeting substance use to alleviate mental health challenges. Limitations, future research directions, and practical implications are discussed.